Impact of brain drain on economic growth and human capital formation in Pakistan - FIAZ, Muhammad Farhan (KDI School, 2017)
Cutting edge speculations of endogenous development have significantly restored the examination of the relations amongst instruction and wellbeing (human capital), movement (cerebrum deplete) and financial development. Human capital and aptitudes matter is endogenous. Just we can say that Brain deplete is the movement of talented HR starting with one nation then onto the next nation. Prepared wellbeing experts are required in all aspects of the world. The objective of this research is to examine, the effect of brain drain on growth of Pakistan’s economy from the year 1980 to 2016. In this study we used economic growth as dependent variable with GPD as its proxy, FDI with proxy of net inflow in million dollars, exports having proxy of net exports in million dollars, exchange rate through official exchange rate and inflation rate for which Consumer Price Index-CPI is used as independent variable. We employed OLS model to the test the effect of brain drain on economic growth. The stationary of variable is showed/confirmed with the help of Augmented Dickey Fuller –ADF Test and Phillip Parron-PP Test. The empirical results shown that there is significant negative relationship between brain drain and economic growth of Pakistan. In addition, the hypothesis has also proved that brain drain and other descriptive variables have significant negative impact on economic growth. However, Labor migration alone does not impact on growth of economy but many other factors also effect directly or indirectly.
Thesis(Master) --KDI School:Master of Public Policy,2017